Book Review: Money Mammoth: Harness the Power of Financial Psychology to Evolve Your Money Mindset, Avoid Extinction, and Crush Your Financial Goals - Robin Raniero Norris (Journal of Financial Therapy, 2021)
The book Money Mammoth focuses on one’s beliefs and habits around money. The authors of the book do not provide financial advice, but rather offer more about the general understanding of how you relate to others and the world around you regarding your financial thoughts and behaviors.